Overcoming Crystallinity Limitations of Aluminium Metal‐Organic Frameworks by Oxalic Acid Modulated Synthesis. Issue 16 (3rd March 2020) - Canossa, Stefano; Gonzalez‐Nelson, Adrian; Shupletsov, Leonid; del Carmen Martin, Maria; Van der Veen, Monique A.
Abstract: A modulated synthesis approach based on the chelating properties of oxalic acid (H2 C2 O4 ) is presented as a robust and versatile method to achieve highly crystalline Al‐based metal‐organic frameworks. A comparative study on this method and the already established modulation by hydrofluoric acid was conducted using MIL‐53 as test system. The superior performance of oxalic acid modulation in terms of crystallinity and absence of undesired impurities is explained by assessing the coordination modes of the two modulators and the structural features of the product. The validity of our approach was confirmed for a diverse set of Al‐MOFs, namely X‐MIL‐53 (X=OH, CH3 O, Br, NO2 ), CAU‐10, MIL‐69, and Al(OH)ndc (ndc=1, 4‐naphtalenedicarboxylate), highlighting the potential benefits of extending the use of this modulator to other coordination materials. Abstract : The chelation of aluminium ions by oxalic acid enables a versatile modulation action, drastically increasing crystal size without undesired framework modifications.